Functionality of the lesson of school instruments on the profession of music teaching - CAN, AJDA AYLİN (ELSEVIER SCIENCE BV, 2012)
Instrument training, benefited most by educationists, is one of the basic resources of music education. Teachers, in line with the education they take, get the opportunity to use their instruments in their classes and by this way to realise the education (Koz, 2007). The lesson of school instrument, in this sense, presents itself as a lesson of three terms with the names School Instruments I-II-III in the curriculums that are applied in departments of music teaching in fine arts education sections in faculties of education. In the study that screening model used, a questionnaire, developed by researches and preformed by taking the opinions of an expert, was conducted to music preservice teachers. Findings about the determination of the current situation of school instruments lesson have contributed to the specification of aspects needing change and improvement for the functionality of the lesson.
Keywords: Music education; School instruments; Music Teacher